Risk stratification for the prediction of overall survival could assist treatment decision‐making at diagnosis of castration‐resistant prostate cancer: a multicentre collaborative study in Japan. (10th August 2020) - Uchimoto, Taizo; Komura, Kazumasa; Fukuokaya, Wataru; Kimura, Takahiro; Takahashi, Kazuhiro; Fujiwara, Yuya; Matsunaga, Tomohisa; Tsutsumi, Takeshi; Tsujino, Takuya; Maenosono, Ryoichi; Yoshikawa, Yuki; Taniguchi, Kohei; et al.
Abstract : Objectives: To assess whether a new risk stratification system according to predictors for overall survival (OS) at the diagnosis of metastatic castration‐resistant prostate cancer (mCRPC) could determine treatment outcomes and assist in treatment decision‐making. Patients and Methods: Two independent clinical cohorts of patients, treated with androgen signalling inhibitors (ASIs: abiraterone and enzalutamide) or docetaxel as a first‐line treatment for mCRPC, were used in this study: a derivation cohort (196 patients with mCRPC) and an external validation cohort (211 patients with mCRPC). Results: Three independent predictors for OS, including duration of initial androgen deprivation therapy <12 months before mCRPC diagnosis, alkaline phosphatase level >350 U/dL and haemoglobin level <11 g/dL at the diagnosis of mCRPC, were defined as risk factors. Patients with zero, one and multiple risk factors were assigned to a favourable‐, intermediate‐ and poor‐risk group, respectively. The median OS values in each risk group were well separated in the derivation cohort ( P < 0.001) as well as in the validation cohort ( P < 0.001). Of a total of 407 patients with mCRPC, 84 were assigned to the poor‐risk group with the median OS of 12 months. In this group, a trend towards longer OS favouring docetaxel compared to ASIs as the first‐line treatment (medians of 17 and 12 months, respectively) was observed. Conclusion: The new risk group stratification system could predict patient survival at the diagnosis of mCRPC. Given the convenience of these risk definitions, physicians may be encouraged to consider these risk groups in daily practice.